Revealing The Main Characters Through The Attitude System in The Folktale Asal Usul Kata Madura - M Hanif Farukhdin; Diah Ikawati Ayuningtias; Sriyono; Rif’ah Inayati (Indonesian Scientific Publication, 2025)
This study aims to reveal the characteristics of the main characters in the folktale Asal Usul Kata Madura through the attitudinal system. This study was conducted because research on how emotion, moral judgments, and evaluations are expressed through language in Indonesian folklore is still very limited. Using the qualitative descriptive method, data were obtained through in-depth reading, identification of clauses containing evaluative elements, and grouping based on three attitude subsystems, namely affect, judgment, and appreciation. The results of the analysis show that affect is the most dominant form of attitude, particularly the expression of insecurity and dissatisfaction, accompanied by moral judgments through judgment, and a small amount of evaluation through appreciation. A total of 35 clauses were identified and analysed from the folklore, consisting of 10 data for Sang Hyang Tunggal, 16 data for Bendoro Gung, and 9 data for Raden Segoro, providing comprehensive data for mapping the attitudes of the main characters. This study concludes that language evaluation in Madurese folklore functions as a means of conveying moral and emotional messages that are passed down from generation to generation. Further studies are recommended to analyse more folklore to enrich the reader’s understanding of evaluative patterns in Indonesian cultural narratives. This study presents a detailed map of attitudes that reveals how character identities are constructed linguistically in the oral tradition of Madura, and offers a systematic model for interindividual analysis that can be applied to other regional folklore in Indonesia.